Metropolización. Acercamiento a la problemática de ciudades en crecimiento, de Everardo Chiapa Aguillón, David Pavel Gómez Granados y José Iván Ramírez Avilés - Islas Ruiz, Alan Suah (El Colegio de México A.C., 2025)
Metropolization is one of the most significant and complex socio-spatial processes in Mexico's recent urban history. Since the late 20th century, the expansion of cities has exceeded municipal administrative boundaries, creating metropolitan areas characterized by growing functional interdependence, but also by fragmented and insufficient institutions.